Business Life Expectancy of Manufacturing Sector from Monteria, Córdoba - Colombia - Chica Urzola, Juan Angel; Serna Mendoza, Ciro Alfonso (European Journal of Sustainable Development, 2019)
The Sustainable Development (SD) of a community is intimately linked to business. This topic turns out to be of great relevance for the economy and sustainability of a certain territory. Companies provide solutions to different factors that take shape within the company, but its origin and consequences are in all dimensions of the SD. The importance of companies in the SD has been recognized by the UN by making them co-responsible 11 of the 17 Sustainable Development Goals, at least - SDGs (UN, 2015). For a company, life expectancy is determined by the different factors that affect it positively or negatively. This is fundamental. What factors influence the duration of the companies? This document presents the results of an investigation to establish the life expectancy of the manufacturing companies of the city of Monteria, Colombia under the period 2013-2018, based on the analysis of the official data contrasted with a hypothesis and interviews with the actors to determine possible causes and relationships. Keywords: Business sustainability, Manufacturing, Business lifetime expectancy